A Facile Liquid Alloy Wetting Enhancing Strategy on Super‐Hydrophobic Lotus Leaves for Plant‐Hybrid System Implementation (Adv. Mater. Interfaces 17/2022). Issue 17 (14th June 2022) - Jiang, Jiajun; Fei, Wenjie; Pu, Menghao; Chai, Zhiping; Wu, Zhigang
Abstract : A Liquid Alloy Wetting Enhancing Strategy on Lotus Leaves In article number 2200516, Jiajun Jiang, Zhigang Wu, and co‐workers propose a facile liquid alloy wetting enhancing strategy and well print liquid alloy circuits on the super‐hydrophobic leaves by introducing a low‐concentration surfactant aqueous solution as an intermediate layer, which provides a new tool for plant‐hybrid implementations and broadens the digitalized application range of plants.